2020
DOI: 10.24191/ijmal.v4i1.9501
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Predictive Validity of English Exit Test: Students' EET Performance and Academic Achievement

Abstract: Graduating students of UiTM are required to sit for English Exit Test (EET) whose objective is to gauge students’ English proficiency level and their readiness for the workplace. Since the test is administered before students finish their studies, it is important to examine if EET has a predictive validity in determining the academic performance of UiTM students. We use the students’ CGPA (Cumulative Grade Point Average) to gauge their academic performance and English language proficiency since English is used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Is there anything else that can be done in universities to better prepare students to meet industry needs? The report in the Australian context by Erling (2015) noted the issue of using standardised language tests, as there seemed to be little evidence to suggest that they are valid and reliable instruments to measure employability even though some may predict academic achievement (Mohamad et al, 2020). This was echoed by a study conducted by Sarudin et al (2013) who found that some employers have considered developing their own in-house standard tests if convincing assurance to current English language standards is lacking, as also mentioned by Erling (2015).…”
mentioning
confidence: 99%
“…Is there anything else that can be done in universities to better prepare students to meet industry needs? The report in the Australian context by Erling (2015) noted the issue of using standardised language tests, as there seemed to be little evidence to suggest that they are valid and reliable instruments to measure employability even though some may predict academic achievement (Mohamad et al, 2020). This was echoed by a study conducted by Sarudin et al (2013) who found that some employers have considered developing their own in-house standard tests if convincing assurance to current English language standards is lacking, as also mentioned by Erling (2015).…”
mentioning
confidence: 99%